Microplastic and adhesive free, multifunctional, circular economy approach-based biomass-derived drinking straws - Rohit Rai; Rahul Ranjan; Chandra Kant; Prodyut Dhar (iScience, 2024)
Summary: Generation of voluminous single-use plastic waste and byproducts from agricultural harvests such as rice straws (RSs) are major global challenges due to their disposal issues, contributing to greenhouse gas emissions, and affecting the ecological system with threats to human health. A scalable, low-cost, and eco-friendly strategy for fabricating cellulose-silica-based drinking straws, free from microplastics and adhesive, through strategic valorization of RS is reported. Functionalization by delignification-cum-crosslinking of RS leads to development of straws with high water stability (∼5 days), solvothermal stability (0°C–95°C), tensile strength (128 MPa), low migration values (<60 mg/kg), improved biodegradability (∼126 days) with reduced wettability and hydrophobicity. RS drinking straws show antibacterial, self-cleaning, self-healing, anti-fizzing, reusable, and generate significantly lower carbon footprint (<99.8% and <53.34% global warming potential than metal and polylactic acid straws). Repurposing of agro-wastes from farms to commercially viable drinking straws which biodegrades after its consumption achieves the goal of circular economy and sustainable development.